A Pentanuclear Cobalt Complex with two [CoII(CH3O)3]– Units Wrapping a Triangular [CoIII3O]7+ Core: Synthesis, Structure, and Magnetic Properties. Issue 12 (25th June 2018) - Yang, Hua; Li, Ruiling; Li, Dacheng; Zeng, Suyuan; Dou, Jianmin
Abstract : The reaction of Hppko (Hppko = phenyl 2‐pyridyl ketone oxime) and CoCl2 · 6H2 O in the CH3 OH solvent with the presence of triethylamine (NEt3 ) at room temperature and the exposure to air resulted in the formation of a new pentanuclear, mixed‐valence cobalt complex with the molecular formula [Co II (CH3 O)3 2 Co III 3 (μ3 ‐O)(ppko)3 Cl2 ]. X‐ray single crystal analysis displays a trigonal bipyramid configuration with the terminal two Co II ions wrapping an triangle [Co III 3 O] 7+ core. The intermolecular C–H··· O and C–H··· Cl interactions form a 2D network framework. The analysis of magnetic susceptibility revealed the dominant antiferromagnetic interactions and strong orbital contribution of Co II ions. Abstract :